If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + 12x + 36 = 7x + 30 + 6x Reorder the terms: 6 + 36 + 12x = 7x + 30 + 6x Combine like terms: 6 + 36 = 42 42 + 12x = 7x + 30 + 6x Reorder the terms: 42 + 12x = 30 + 7x + 6x Combine like terms: 7x + 6x = 13x 42 + 12x = 30 + 13x Solving 42 + 12x = 30 + 13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13x' to each side of the equation. 42 + 12x + -13x = 30 + 13x + -13x Combine like terms: 12x + -13x = -1x 42 + -1x = 30 + 13x + -13x Combine like terms: 13x + -13x = 0 42 + -1x = 30 + 0 42 + -1x = 30 Add '-42' to each side of the equation. 42 + -42 + -1x = 30 + -42 Combine like terms: 42 + -42 = 0 0 + -1x = 30 + -42 -1x = 30 + -42 Combine like terms: 30 + -42 = -12 -1x = -12 Divide each side by '-1'. x = 12 Simplifying x = 12
| (2x-7)-(3x+5)=5(x-3) | | f(x)=x^4-9x^2+18 | | 8a=4b-20 | | 6-10x=0 | | 2x+66=5x+9 | | (x+2)*(5-3x)= | | C^2-15c-54=0 | | 4(x+6)-x(x+6)=0 | | lg(2x)=4.5 | | 4(n-3)-3n=1+2 | | cos^2x+5cosx=1 | | 15x-17=22 | | 10+7f=8f | | 2x+18=-3y | | 3*(5*x-7)+2*(2*x+17)=5*(3*x-4)+37 | | (3y-5)(8-y)=0 | | 4(x)=3x-1 | | X^2+x=0.24 | | 3(1)-2(6)=9 | | 5x+1=-16 | | 6(y+2)=-3(6y-1)+6y | | 13X=10X-9 | | Y=-x(x-2) | | 3(1)+2(6)=9 | | 3x^2+5x-2y^2=0 | | -x(0)+5y=15 | | -x+0=15 | | 2y-42=4 | | a+4-a(a+4)=0 | | 5h+24=-8(b-6)+6b | | sin(x)=0.5625 | | 1a-4b+2c=0 |